Illness Perception and Quality of Life among Chronically Ill Patients: A Study of Diabetics and Hypertensives at Korle-Bu Teaching Hospital - Quaye, M.G. (University of Ghana, 2015)
The aim of the study was to assess the quality of life among chronically ill patients. Specifically the study examined the effects of illness perception, socio-economic status, compliance with medication, religiousity and gender of the patient on quality of life. Ninety participants were selected from the Korle Bu Teaching Hospital to take part in the study. The ninety participants consisted of 30 diabetics, 30 hypertensives and 30 participants who were neither hypertensives nor diabetics as the control group. Data was analyzed using Pearson correlation, the independent t-test and the ANOVA. Findings indicated that healthy participants had higher quality of life than hypertensives and diabetics. Diabetics also had lower quality of life than hypertensives. Patients with chronic illness who had higher level of socioeconomic status did not differ from those with lower level of socioeconomic status on quality of life. No significant difference was found in quality of life among chronically ill males and chronically ill females. There was a positive relationship between illness perception and quality of life. Compliance with medication had positive relationship with quality of life. The relationship between illness perception and quality of life was partially mediated by medication compliance. Highly religious chronically ill patients had higher quality of life than low religious chronically ill patients. In conclusions, health professionals should pay more attention to patients’ quality of life and help them develop a positive perception about their illness and comply with treatment regimen.
Thesis(MPHIL)-Methodist University College, Ghana, 2015
Keywords: Diabetics; Hypertensives; Illness Perception; Chronically Ill Patients